PENGARUH PUPUK ORGANIK CAIR TERHADAP PERTUMBUHAN DAN HASIL DUA VARIETAS TANAMAN JAGUNG MANIS (Zea mays saccharataSturt) - Irna Syofia; Asritanarni Munar; Muhammad Sofyan (AGRIUM: Jurnal Ilmu Pertanian, 2014)
This study aimed to determine the effect of organic manure on growth and yield of two varieties of sweet corn (Zea Mays saccharata Sturt). Implemented in Jl. Door Air IV B Simalingkar village, subdistrict of Medan Medan Johor, with ± 25 m altitude above sea level in April 2013 to July 2013 using the design Plots Divided (RPT). Factors studied consists of two varieties and liquid organic fertilizer. The difference between the two varieties (V) as the main plot consists of two levels and V1 = V2 = jamboree Varieties Varieties bonanza and given liquid organic fertilizer is fertilizer Santamicro (S) as the subplot consisted of 4 levels ie at concentrations of 0, 1, 2, and 3 ml / liter of water, each with a symbol S0, S1, S2, and S3. The results showed that the liquid organic fertilizer higher Santamicro gave the highest yield in ear length, ear diameter, ear weight per plant, and weight of cobs per plot with a concentration of 3 ml / liter of water. Plant sweet corn varieties jamboree gives a higher influence on plant height and number of leaves. The combination of organic liquid fertilizer concentration Santamicro with two sweet corn varieties provide tangible interactions on the growth and yield of sweet corn. Keywords: santamicro fertilizer, varieties, growth, yield, sweet corn